2010
DOI: 10.1111/j.1540-8191.2009.00972.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Myocardial Ischemia-Reperfusion Injury by Mechanical Tissue Resuscitation Using Sub-Atmospheric Pressure

Abstract: Treatment of ischemic myocardium with MTR, for a controlled period of time during reperfusion, successfully reduced the extent of myocardial death after acute myocardial infarction. These data provide evidence that MTR using subatmospheric pressure may be a simple, efficacious, nonpharmacological, mechanical strategy for decreasing cardiomyocyte death following myocardial infarction, which can be delivered in the operating room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 18 publications
(30 reference statements)
3
16
0
Order By: Relevance
“…MTR administered immediately upon reperfusion has previously been shown to reduce myocardial edema, infarct size, and apoptosis . Here, MTR reduced infarct size by nearly 50% even though treatment was delayed for 90 minutes (half of the total reperfusion period).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…MTR administered immediately upon reperfusion has previously been shown to reduce myocardial edema, infarct size, and apoptosis . Here, MTR reduced infarct size by nearly 50% even though treatment was delayed for 90 minutes (half of the total reperfusion period).…”
Section: Discussionmentioning
confidence: 73%
“…Hemodynamics and arterial blood gases were recorded at baseline, middle, and end of ischemia (mid‐ and end‐isc), as well as at 30 (R30), 60 (R60), 120 (R120), and 180 (R180) minutes of reperfusion. MTR‐treatment was applied 90 minutes after reperfusion and was accomplished using a polyvinyl–alcohol sponge, nitrile sheet, and a vacuum tube attached to a computer‐controlled vacuum pump as previously described . Evicel glue (Ethicon, Somerville, NJ, USA) was used to seal the edges of the nitrile to the myocardium creating an airtight patch.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study using a rat cremaster model supports the contention that this phenomenon is real and is remedied at the microscopic level by early use of negative pressure wound therapy by enhancing the resolution of interstitial edema and clearance of albumin from the third space [31]. Relevant to these mechanisms, animal studies have shown successful use of negative pressure wound therapy in favorably preserving tissue in the setting of myocardial infarction or brain tissue loss after closed head trauma [3,4,34]. Given the evidence provided in these settings, one may attribute some of the diminution in infection and improvements in tissue healing attributable to negative pressure wound therapy to avoidance of secondary necrosis.…”
Section: Corroborations From Basic Science and Other Disciplinesmentioning
confidence: 86%